2012
DOI: 10.1093/ehjci/jes133
|View full text |Cite
|
Sign up to set email alerts
|

Incidental extra-cardiac findings on clinical CMR

Abstract: IEFs are common, requiring further investigation in a substantial minority. The incidence of highly significant findings in this study was low (∼1%), and similar to the reported incidence in the computed tomography literature. No significant difference was found between the reporting rates of IEFs between different specialties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 15 publications
1
32
2
Order By: Relevance
“…3). The prevalence of IF in our study population is greater than that in several studies looking at the rate in clinically indicated CMR [10, 11, 13]. In fact, it is more than seven times greater than the rate reported by Chan in a clinically robust study of 1534 consecutive clinically indicated CMR studies (59.0 % vs 7.6 %) [10].…”
Section: Discussioncontrasting
confidence: 59%
“…3). The prevalence of IF in our study population is greater than that in several studies looking at the rate in clinically indicated CMR [10, 11, 13]. In fact, it is more than seven times greater than the rate reported by Chan in a clinically robust study of 1534 consecutive clinically indicated CMR studies (59.0 % vs 7.6 %) [10].…”
Section: Discussioncontrasting
confidence: 59%
“…Mean age and sex ratio were not different across studies. Ten studies used 1.5T scanners, one study used both 1.5 and 3T scanners, and one did not report field strength . MR sequences used in the studies are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…MR sequences used in the studies are summarized in Table . Two studies were prospective, nine retrospective, and one did not specify prospective or retrospective design . Seven studies were based on MR images review, four were based on MR reports review, and one on both .…”
Section: Resultsmentioning
confidence: 99%
“…However, it is noteworthy that this study was carried out on well, asymptomatic patients for research purposes, whereas six out of the seven previously published studies have looked for CSECFs in patients having clinically indicated MRI scans. 2,3,[5][6][7][8] In some instances these patients were intubated, which would increase the chance of finding pathology such as atelectasis, pleural effusions and pneumonias which were often the most common findings. Dewey et al 4 found a prevalence of 2% CSECFs in a research group of older patients, mean age 63 years.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CSECFs reported in previous studies is between 1.1% and 21%. [2][3][4][5][6][7][8] Whilst these studies have looked at the prevalence in the general population, no study has looked specifically at an HIV-positive population.…”
Section: Introductionmentioning
confidence: 99%